Crystallization of founders' values applied to corporate culture: the meta-analysis of case study - Mochammad Reza Zulfikar,; Suryanto, Suryanto; Suaedi, Falih (Technium Social Sciences Journal, 2023)
Forming the company's fundamental values is the first problem in building a corporate culture, including in a corporate holding. This success must be efficiently maintained and passed down to all employees from top management to lower-level executors, even if necessary, in the framework of organizational sustainability for the company. Furthermore, the founder's responsibility is to add new values according to the times to continue growing, developing, and satisfying stakeholders. The purpose of this study is to analyze the crystallization of Founders' values applied to corporate culture. This research used a qualitative approach with a case study meta-analysis method. This study concluded that the crystallization of corporate culture was built and implemented based on founders' values, which comes under the influence of several factors. Some of them include 1.) The mentor factor of the company founder; 2.) The family background of the company founder; 3.) The factors of the problematic life background of the company founder; 4.) The factors of the formal educational background of the company founder; 5.) The background factor for the founder's daily activities; 6.) The Factors of previous company founders' business experience; 7.) The factors causing starting a business; 8.) Any other negative background factor of the company founder.